Acceptance of the COVID-19 vaccine booster dose and associated factors among the elderly in China based on the health belief model (HBM): A national cross-sectional study - Qin, Chenyuan; Yan, Wenxin; Du, Min; Liu, Qiao; Tao, Liyuan; Liu, Min; Liu, Jue (Frontiers in Public Health, 2022)
Background: The reluctance of people to obtain solid immunity induced by vaccines represents a fundamental challenge to containing the spread of SARS-CoV-2, including the highly mutated variants. We aimed to assess vaccination acceptance and associated factors for the booster dose of the COVID-19 vaccine among older people (≥60 years old) in China, providing a theoretical and practical reference for universal vaccination policy. Methods: This national anonymous survey was conducted in mainland China using a stratified random sampling method from May 25 to June 8, 2022. People who were 60 years old and above were the target population. The chi-square test and Cochran-Armitage test for trend were used to compare and examine vaccine acceptance rates by characteristics. All independent variables were added to our multivariable models to assess factors associated with acceptance toward the booster dose via a backward stepwise method (P < 0.2). Results: Of 3,3 21 eligible participants, 82.8% (95% CI: 81.5-84.1%) were willing to receive the booster shots of COVID-19 vaccine. Concerns about contraindications (38.3%), vaccine safety (32.0%), and limited movements (28.0%) were the main reasons for vaccine hesitancy. Nearly one-third still believed that the booster dose was unnecessary after receiving initial vaccination. The major factors affecting the acceptance rate toward the booster dose were occupation, time for social media, vaccination history, high knowledge score on COVID-19 and vaccines. In addition, older adults with a low level of perceived barriers (aOR=1.86, 95% CI: 1.03-3.38), a high level of perceived benefit (aOR=2.31, 95% CI: 1.38-3.87), and higher cues to action (moderate: aOR=2.22, 95% CI: 1.39-3.56; high: aOR=5.46, 95% CI: 3.44-8.67) were more likely to accept the booster dose. For the over 70s, rising awareness of susceptibility could be a better gateway to improve their willingness to get vaccinated. Conclusions: Targeted public health measure is a priority to improve the vaccination coverage of valid immunity among the aged population, not only to prevent infection and poor prognosis caused by emerging variants, but also to reduce the huge disease and economic burden caused by the long-term sequelae after SARS-CoV-2 infection.